ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL “PERTEMUAN DUA HATI” KARYA NH. DINI - Nurfitriany '; Otang Kurniaman; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : Character education became a main issue in education in Indonesia. Social phenomena that we can see now a days is the low values of the characters in self-learners. Examples of problems that we often encounter in our environment is many students  violates the religion norm, naughtiness teenage, absence school. This study aims to describe the values of character education in “pertemuan dua hati” by Nh. Dini’s novel which used qualitative descriptive method. Data collection techniques used in this research method is a technique of reading, technical notes, technical literature. In this study, there are three ways to analyze the data: (1) data reduction, (2) Model display, (3) verification conclusion. The study of the novel "Pertemuan Dua Hati” by Nh. Dini researchers 15 character education in this novel such as: religious, honest, discipline, hard working, creative, independent, patriotism, respect for the achievements, friends / communicative, love peace, love reading, environmental caring, social caring, and responsibility. character education value that dominates the novel "pertemuan dua hati" by Nh. Dini is the character of responsibility. In the character of responsibility are found there are 11 indicators that indicate the character values of responsibility. Values characters responsibility that owned bu Suci can change his students named Wakasito be a better. Because  a teacher is not just teaching but teacher are also guide, educate, directing students to be better. The values of character education that is found in the novel “Pertemuan Dua Hati "by Nh. Dini tangible behaviors performed by a character to handle the events and in various forms of interaction between a character to another characters on narration.